Pelatihan Menulis Makalah dan Jurnal Ilmiah dalam Meningkatkan Kemampuan Literasi Mahasiswa Fakultas Manajemen Pendidikan Islam - Winarto Winarto; Suyitno Suyitno; Linta Zahria (Jurnal Kemitraan Masyarakat, 2024)
This community service aims to develop students' writing literacy. The main focus of this service is training in effective sentence writing and the application of punctuation. This writing training involved 15 MPI students of the Faculty of Islamic Religion, Islamic University of Balitar Blitar. The training was held for 2 meetings within 1 full day in November 2024. The training in writing scientific papers and journals for students of the Faculty of Islamic Religion (FAI) Unisba includes several stages, namely pretest (writing papers), identification of academic vocabulary, analysis of scientific sentence structure, analysis of the use of punctuation, intensive practice in the preparation of vocabulary, sentences, and punctuation marks according to academic rules, and posttest (writing papers or journals). This activity is carried out in groups and individuals by applying learning strategies and media that are interesting and relevant to the academic needs of students. After participating in the training (posttest), 80% of students were able to reach a proficient and proficient level in writing scientific papers and journals. These results show a significant increase compared to the achievement before the training (pretest), where 73% of students were only able to reach the basic level. Based on these results, it is recommended to the Faculty of Islamic Religion Unisba to intensify the academic literacy training program, especially in writing scientific papers and journals. Students who have the potential to excel in academic writing need to continue to hone their skills through continuous coaching, while students who still need special assistance can be given additional programs to improve the quality of their skills.